Analisis Faktor Yang Mempengaruhi Output Pertanian Tanaman Pangan Di Indonesia - Fadhil Novesa; Sri Ulfa Sentosa (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the effect of harvested rice area, fertilizer use, agricultural machinery and equipment, and agricultural labor on food crop agricultural output in Indonesia. The study employs panel data covering 33 provinces in Indonesia during the 2019–2023 period. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) and the Agricultural Information System Data Center. The dependent variable in this study is food crop agricultural output, while the independent variables include harvested rice area, fertilizer, agricultural machinery and equipment, and agricultural labor. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM) approach. The results indicate that, partially, harvested rice area has a negative and significant effect on food crop agricultural output in Indonesia. Meanwhile, fertilizer has a negative but insignificant effect, agricultural machinery and equipment have a positive but insignificant effect, and agricultural labor has a negative and insignificant effect on food crop agricultural output. Simultaneously, all independent variables have a significant effect on food crop agricultural output in Indonesia. These findings suggest that agricultural production factors collectively play an important role in determining the level of food crop agricultural output in Indonesia.